Distinct and enhanced ultraviolet to visible ZnS-porous silicon (PS):p-Si hybrid metal-semiconductor-metal (MSM) photodetector. (2021) - Das, M.; Sarmah, S.; Sarkar, D.
Highlights: Fabrication of ZnS-Porous silicon (PS):p-Si Heterostructure (HT) Al and Au Schottky contacts on ZnS-PS:p-Si HT. Specific UV to Visible photodetector from Al + Au/ZnS-PS:p-Si HT. Abstract: Present article reports distinct and enhanced ultraviolet to visible light sensing property of metal-semiconductor-metal (MSM) based ZnS-PS:p-Si hybrid heterostructure. PS:p-Si heterostructure is prepared using electrochemical anodization technique by alternate variation of etching current density within the limit of 17.2–22.1 mA cm −2 . ZnS (99.99% purity) in powder form is deposited on PS:p-Si surface via thermal evaporation technique under a chamber pressure of 2 × 10 −5 m bar. To achieve MSM configuration Au electrode of ∼8 nm and Al electrode of ∼22 nm thickness are successively coated on top of ZnS-PS:p-Si surface using a shadow mask with dimension of 6 × 6 mm. Morphological features of the heterostructure are observed and analysed using cross section FESEM. This gives thickness of the deposited ZnS layer as around ∼110 nm on ∼540 nm thick PS:p-Si structure. These also confirm uniform interface between the two i.e, ZnS and PS:p-Si layers. Cross sectional EDX analysis indicates diffusion of ZnS particles into the PS layer. Optical analysis observed via UV–Visible spectroscopy gives bandgap (obtained through Tauc plot) of the bare ZnS film to be 3.4 eV with 70–90% transparency in the visible region (390–700 nm). Optical reflectance spectrum of the prepared heterostructure shows decreased reflectivity compared to that of the bare PS:p-Si structure which is itself 20–30% less compared to bulk silicon. Spectral response measured for the wavelength range of 200–500 nm gives distinct and enhanced responsivity peak values of ∼0.94 and ∼1.12 AW −1 at 365 nm (UV) and 400 nm (visible) compared to ∼0.5 AW −1 (maximum at 400 nm) of bare PS:p-Si MSM structure for bias voltage of −4 V. The response and recovery times of the heterostructure are found to be 0.54 ± ( 4.3 × 10 - 4 ) s, 0.38 ± 9.5 × 10 - 5 s and 0.50 ± 2.8 × 10 - 4 s, 0.35 ± 6.5 × 10 - 5 s under UV and visible irradiations.